Chief Financial Officers and Corporate Sustainability: A Literature Review and Research Agenda - Alrazi B.; Mat Husin N.; Mohd Ali I.; Nik Azman N.A.N.; Mohd Nor M.N. (IOP Publishing Ltd, 2023)
Societal and environmental risks dominated the top 10 risks in both likelihood and impact, according to the surveys conducted by the World Economic Forum. Against this background, there have been many cases demonstrating the disastrous financial impact of organisational failure to address societal and environmental risks. As a person whose responsibility is to assess financial risks of the organisation, there is increasing expectation for the Chief Financial Officer (CFO) to lead sustainability strategy and initiatives. This research serves to review the literature which highlights the roles and characteristics of CFOs essential for corporate sustainability. Drawing upon this and related literature examining the influence of CFOs on other accounting practices, it proposes a framework illustrating the potential relationships between CFO characteristics and corporate sustainability. Published under licence by IOP Publishing Ltd.